The Interplay among HR Sustainability Initiatives, Intention to use of Energy Resources, Environmental Consciousness, and Environmental Performance - Alzghoul, Amro; Khaddam, Amineh A.; Al-Kasasbeh, Omar (International Journal of Energy Economics and Policy, 2024)
This is major research on the three constructs of intention to use energy resources efficiently and environmental consciousness, as well as, how they collectively interact towards environmental performance in the context of HR sustainability initiatives. The study, using quantitative analysis data collected from different organizations, how these factors collectively influence sustainable outcomes. The analysis results strongly support the proposed hypotheses since the moderating effects from environmental consciousness and energy efficiency intentions further strengthen the relationship between HR sustainability and environmental performance. They complement HR practices that seek to intensify awareness of environmental protection and the efficient use of energy within organizations. These findings shed light on the synergistic effects of HR sustainability initiatives combined with a "green" workforce keen on energy efficiency, providing an abundance of opportunities for global environmental performance improvement. It adds perspective to the current debate about how values-based HR practices contribute to organizational sustainability and offers insight to those organizational practitioners considering this course of action. This research delves into what an amalgamated approach for organizational sustainability might look like, given the combined positive effects of sustainable HR practices, environmental consciousness, and efficient energy use in driving enhanced environmental outcomes.